2006
DOI: 10.1373/clinchem.2005.057950
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, Endothelial Nitric Oxide Synthase Polymorphism, and Risk of Coronary Artery Disease

Abstract: Background:Hyperhomocysteinemia is an independent, graded risk factor for coronary artery disease (CAD). The G894T variant of endothelial nitric oxide synthase (eNOS) was postulated to be associated with hyperhomocysteinemia and could influence individual susceptibility to CAD. The aims of this study were to investigate (a) the relationship of the eNOS G894T polymorphism with the presence and the severity of CAD and (b) the possible relationship between hyperhomocysteinemia and the eNOS G894T variant for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 41 publications
9
28
2
Order By: Relevance
“…Moreover, it was observed that 5% of control subjects had TT genotype, and 60% of them had GG genotype and this is consistent with the rates established among the Tunisian population. 31,32 These results are in agreement with the findings of Neugebauer et al 21 and Shin Shin et al, 33 who reported an association between the eNOS gene polymorphism and the progression of DN in Japanese and Korean type 2 diabetic patients, respectively. These notions were supported by recent reports.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it was observed that 5% of control subjects had TT genotype, and 60% of them had GG genotype and this is consistent with the rates established among the Tunisian population. 31,32 These results are in agreement with the findings of Neugebauer et al 21 and Shin Shin et al, 33 who reported an association between the eNOS gene polymorphism and the progression of DN in Japanese and Korean type 2 diabetic patients, respectively. These notions were supported by recent reports.…”
Section: Discussionsupporting
confidence: 91%
“…However, in one study in our lab on the same polymorphism GG dominates over GT and TT genotypes [9]. Likewise in several other studies, GG dominates over GT and TT genotypes [10,11,12]. In our study, the distribution pattern did not obey Hardy Weinberg equilibrium.…”
Section: Discussioncontrasting
confidence: 65%
“…More of the complications were due to the direct implication of homocysteine on the endothelial damage. Hyperhomocysteinemia is associated with vascular diseases such as hypertension, cerebrovascular accidents, peripheral vascular diseases, as well as early pregnancy loss and placental abruption [9][10][11][12][13]. Abruption was found in 2 patients in the study conducted by Sunita et al [6].…”
Section: Discussionmentioning
confidence: 99%